THE INFLUENCE OF CAPITAL STRUCTURE AND FINANCIAL PERFORMANCE ON EARNINGS MANAGEMENT - Ramdona, Sinta Sri; Larasati, Meita; Ramdani, Safier (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: This research aims to analyze the influence of capital structure and financial performance on earnings management practices in non-cyclical consumer sector companies listed on the Indonesia Stock Exchange. Method: This research uses a quantitative method, involving 118 samples of annual report data for the period 2021- 2022. Results: The results of the analysis indicate that capital structure has a significant negative impact on earnings management. On the other hand, financial performance has a significant positive impact on earnings management. Although both variables have a significant simultaneous effect, the coefficient determination shows that most of the variation in earnings management is influenced by other factors, such as regulation and corporate governance. Novelty: The novelty in this research lies in the use of the Stubben formula to measure earnings management, which provides a deeper perspective on the practice of earnings manipulation within companies.